Preparation method of ultra-microporous alumina nanofiber

CN118084029BActive Publication Date: 2026-10-09PETROCHINA CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211503992.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-28
Publication Date
2026-10-09
Estimated Expiration
2042-11-28

AI Technical Summary

Technical Problem

[0008]有鉴于此,本发明提供一种超微孔氧化铝纳米纤维的制备方法,以克服现有技术中采用固相法无法制得具超微孔结构的氧化铝纳米材料的问题

Benefits of technology

[0022] Beneficial Effect 1: The preparation method of ultraporous alumina nanofibers provided by this invention separates the aluminum source, boehmite, from the modifier (providing sufficient upward diffusion space for the decomposition gas of the modifier), and places the modifier at the bottom of the boehmite. The gas generated by the decomposition of the modifier diffuses into the boehmite for a contact reaction. During the reaction, the gas generated by the decomposition of the modifier inserts into the crystal lattice of the boehmite and grows along a specific crystal orientation to obtain an alumina precursor. This alumina precursor is then subjected to vacuum heating decomposition and muffle furnace calcination to form alumina nanofibers with ultraporous structures. The alumina material prepared by the method provided by this invention not only has an ultraporous structure, high specific surface area, and narrow pore size distribution, but also does not require the addition of organic template agents during the preparation process, which is of great significance for the industrial preparation of ultraporous alumina.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118084029B_ABST
    Figure CN118084029B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of ultra-microporous alumina nanofiber, which comprises the following steps: placing a modifier at the bottom of a polytetrafluoroethylene reactor, placing pseudo-boehmite dry powder wrapped with filter paper at the upper layer of the polytetrafluoroethylene reactor and fixing the pseudo-boehmite dry powder, then placing the polytetrafluoroethylene reactor into a closed crystallization kettle for a crystallization reaction, drying, vacuum heat decomposing the obtained alumina precursor, and calcining to obtain the ultra-microporous alumina nanofiber. The alumina material prepared by the preparation method has not only an ultra-microporous structure, a high specific surface and a narrow pore size distribution, but also does not need to add an organic template agent in the preparation process, which is of great significance for the industrialized preparation of the ultra-microporous alumina.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanofiber materials technology, and specifically to a method for preparing ultraporous alumina nanofibers. Background Technology

[0002] Alumina, due to its abundant porous structure and tunable surface acidity / alkalinity, is widely used as a catalyst, catalyst support, in wastewater purification, gas separation, automotive exhaust emission reduction systems, and waste gas purification. Traditional γ-Al₂O₃ suffers from low specific surface area and excessively wide pore distribution, failing to meet the specific requirements for selectivity, stability, and reaction contact area in catalytic processes. Therefore, the synthesis of alumina with a larger specific surface area and narrower pore size distribution holds great promise for future applications.

[0003] Ultraporous materials are porous nanomaterials. In recent years, due to their unique advantages in shape-selective catalysis and adsorption separation, ultraporous alumina materials have become a focus of research. For example, Chinese patent document CN103073036A discloses an ultraporous alumina material with high specific surface area. Specifically, it employs a solvent evaporation-induced self-assembly method, utilizing inexpensive nonionic surfactants. During the hydrothermal synthesis and self-assembly process, an aluminum source is added. By introducing organic carboxylic acids and adjusting the temperature and time of solvent evaporation-induced self-assembly, the hydrolysis-polymerization process of the aluminum source is controlled. This results in a relatively larger number of incompletely polymerized aluminum hydroxyl groups (Al-OH) at the organic-inorganic interface layer, which interact with the nonionic surfactant micelles through hydrogen bonding, forming an ultraporous alumina material with a high specific surface area. The final synthesized alumina has an average pore size of 1.7 nm and a specific surface area of ​​550.1 m² after high-temperature calcination. 2 / g. However, the organic template agent used in this method is not environmentally friendly, and the resulting material cannot simultaneously possess both thermal stability and catalytic activity.

[0004] Chinese patent document CN108217702A discloses a method for synthesizing basic aluminum ammonium carbonate via hydrothermal crystallization of urea and boehmite. The resulting ultraporous alumina material, after calcination at 500℃, has a specific surface area as high as 781.6 μm. 2 / g, and no organic template agent is required. However, this alumina material is synthesized using a liquid-phase method, which generates a lot of wastewater during industrial scale-up, increasing the cost of wastewater treatment.

[0005] Chinese patent document CN109292802A discloses a green process for preparing alumina materials with high specific surface area. Specifically, the process involves: a) preparing a clarified solution using amide compounds (formamide, acetamide, urea, etc.) as modifiers; b) adding boehmite to the clarified solution at a specific molar ratio, stirring until the solution is homogeneous, and then transferring it to a crystallization reactor; c) washing and drying the crystallized solid to obtain basic aluminum ammonium carbonate (AACH), and recycling the resulting mother liquor; d) cooling the mother liquor, adding a certain amount of modifier, and recycling it; repeating steps b and d, ultimately obtaining a specific surface area as high as 812.5 μm. 2 / g of basic aluminum ammonium carbonate decomposes upon heating to obtain a specific surface area of ​​681.8m. 2 / g high specific surface area alumina. This method achieves the recycling of the mother liquor after the reaction, with no waste liquid discharge, and is energy-saving and environmentally friendly. However, this method is relatively cumbersome and has low production efficiency.

[0006] Chinese patent document CN111233017A discloses a process for synthesizing monoclinic basic ammonium aluminum carbonate and its pyrolysis preparation of porous alumina. Aluminum hydroxide powder and a modifier are ground and mixed evenly, transferred to a crystallization kettle, and subjected to a solid-phase reaction. After drying, an alumina precursor is obtained. Finally, the obtained alumina precursor is calcined to obtain the porous alumina material. This material has a high specific surface area (631.9 m²). 2 / g) and macropore volume (1.9cm) 3 / g), but this material does not have an ultraporous structure.

[0007] There are currently no reports of successful synthesis of ultraporous alumina via solid-state methods. Most alumina synthesized by existing solid-state methods is mesoporous alumina, and it cannot simultaneously possess the characteristics of high specific surface area and narrow pore size distribution. Summary of the Invention

[0008] In view of this, the present invention provides a method for preparing ultraporous alumina nanofibers to overcome the problem that the existing solid-state method cannot produce alumina nanomaterials with ultraporous structures.

[0009] To achieve the above objectives, the present invention provides a method for preparing ultraporous alumina nanofibers, comprising the following steps:

[0010] The modifier is placed at the bottom of the polytetrafluoroethylene reactor. The pseudoboehmite dry powder is wrapped with filter paper and placed on the upper layer of the polytetrafluoroethylene reactor and fixed. Then the polytetrafluoroethylene reactor is placed in a sealed crystallization kettle for crystallization reaction and dried to obtain alumina precursor (basic aluminum ammonium carbonate, abbreviated as AACH).

[0011] The alumina precursor is decomposed by vacuum heating and then calcined to obtain the ultraporous alumina nanofibers.

[0012] In the preparation method of ultraporous alumina nanofibers provided by this invention, the distance between the boehmite powder and the modifier is not specifically limited, as long as they do not come into direct contact, allowing space for the gas generated by the decomposition of the modifier to rise and diffuse. The thickness of the boehmite powder layer is not specifically limited; it can be adjusted according to the inner diameter and height of the polytetrafluoroethylene (PTFE) reactor to control contact with the gas. The specific method for achieving the distance between the boehmite powder and the modifier inside the PTFE reactor is not specifically limited, as long as they are kept at a fixed distance and no impurities are introduced during the reaction. For example, a glass container or a PTFE support can be placed inside the PTFE reactor to support the boehmite powder, provided that the glass container or the PTFE support does not react with the decomposed modifier and does not decompose under the entire reaction temperature and pressure.

[0013] In the preparation method of ultraporous alumina nanofibers provided by the present invention, filter paper is used to coat boehmite powder. On the one hand, this prevents the boehmite powder from falling and directly contacting the modifier, which would result in the final material not having an ultraporous structure. On the other hand, it allows the gas generated by the decomposition of the lower layer modifier to diffuse through the pores of the filter paper into the boehmite to participate in the reaction.

[0014] This invention does not have special requirements for the aluminum source; industrial boehmite can be used. Using industrial boehmite as the aluminum source can reduce production costs.

[0015] Optionally, the modifier in this invention is an ammonium salt; the ammonium salt can be any conventional one used in the industry and is not specifically limited, but preferably the ammonium salt is selected from at least one of ammonium carbonate, ammonium bicarbonate, ammonium acetate, ammonium carbamate, ammonium oxalate, ammonium formate, ammonium citrate, and ammonium tartrate.

[0016] Optionally, the molar ratio of the modifier to the Al element in the pseudoboehmite is 1.5 to 20:1.

[0017] Optionally, the crystallization reaction parameters described in this invention are not specifically limited. The crystallization parameters for preparing ultraporous alumina nanofibers using conventional solution methods in the industry can be adjusted according to actual conditions. The crystallization reaction temperature recommended by this invention is 50–180℃, such as 60℃, 80℃, 70℃, 90℃, 110℃, 120℃, 140℃, 160℃, 150℃, 170℃, etc.; the time is 6–48h, such as 10h, 12h, 15h, 18h, 20h, 22h, 25h, 28h, 30h, 35h, 40h, 48h, etc.

[0018] Optionally, the material obtained after the crystallization reaction is completed is dried, mainly to remove the small amount of water generated during the decomposition of the modifier. The specific drying temperature and time are not limited, as long as the water in the system can be removed. The drying temperature recommended by this invention is 60-200℃.

[0019] Optionally, the parameters for vacuum thermal decomposition of the alumina precursor in this invention are not specifically limited. The decomposition parameters for preparing ultraporous alumina nanofibers using the conventional liquid-phase method can be adopted. The recommended vacuum thermal decomposition temperature for the alumina precursor is 150–350℃, such as 160℃, 310℃, 180℃, 320℃, 200℃, 220℃, 240℃, 280℃, etc. The recommended vacuum thermal decomposition time for the alumina precursor is 1–5 h, such as 2 h, 3 h, 4 h, 4.5 h, etc. The recommended heating rate for vacuum thermal decomposition of the alumina precursor is 1–10℃ / min, such as 3℃ / min, 5℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, etc.

[0020] Optionally, the calcination described in this invention can be performed using the conventional liquid-phase method for preparing ultraporous alumina nanofibers. The calcination method recommended in this invention is carried out in a muffle furnace at a temperature of 400–800°C for 2–6 hours, such as 450°C, 500°C, 650°C, 750°C, 700°C, etc.

[0021] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0022] Beneficial Effect 1: The preparation method of ultraporous alumina nanofibers provided by this invention separates the aluminum source, boehmite, from the modifier (providing sufficient upward diffusion space for the decomposition gas of the modifier), and places the modifier at the bottom of the boehmite. The gas generated by the decomposition of the modifier diffuses into the boehmite for a contact reaction. During the reaction, the gas generated by the decomposition of the modifier inserts into the crystal lattice of the boehmite and grows along a specific crystal orientation to obtain an alumina precursor. This alumina precursor is then subjected to vacuum heating decomposition and muffle furnace calcination to form alumina nanofibers with ultraporous structures. The alumina material prepared by the method provided by this invention not only has an ultraporous structure, high specific surface area, and narrow pore size distribution, but also does not require the addition of organic template agents during the preparation process, which is of great significance for the industrial preparation of ultraporous alumina.

[0023] 2. This invention synthesizes alumina with an ultraporous structure via a solid-state method, successfully solving the problems of existing solid-state methods that produce alumina without an ultraporous structure and cannot simultaneously possess both high specific surface area and narrow pore size distribution. The alumina precursor synthesized in this invention has a specific surface area as high as 684.04 m². 2 / g, after high-temperature calcination, the ultraporous alumina nanofibers have a specific surface area of ​​544.7 μm. 2 / g, with an average pore size of 2.3nm. Attached Figure Description

[0024] Figure 1 The N2 adsorption-desorption isotherms of AACH prepared in Examples 1-7 of this invention;

[0025] Figure 2 The pore size distribution curves of AACH obtained in Examples 1-7 of this invention are shown.

[0026] Figure 3 The XRD diffraction patterns of AACH prepared in Examples 1-3 are shown below.

[0027] Figure 4 The XRD diffraction patterns of AACH prepared in Examples 4-7 are shown below.

[0028] Figure 5 The N2 adsorption-desorption isotherms of the ultraporous alumina nanofibers prepared in Examples 1-3;

[0029] Figure 6 The diagram shows the pore size distribution of the ultramicroporous alumina nanofibers prepared in Examples 1-3.

[0030] Figure 7 The XRD diffraction patterns of the ultraporous alumina nanofibers prepared in Examples 1-3 are shown below.

[0031] Figure 8 The images shown are SEM images of the ultraporous alumina nanofibers prepared in Examples 2-3. Detailed Implementation

[0032] The present invention will now be described in detail through embodiments. It should be noted that the following embodiments are only for further illustration of the present invention and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above description.

[0033] The technical solution of the present invention will be further described in detail below through specific embodiments. Where specific experimental steps or conditions are not specified in the embodiments, they can be performed according to the conventional experimental steps or conditions described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.

[0034] In this invention, the inner diameter and height of the polytetrafluoroethylene (PTFE) reactor are not specifically limited, nor is the distance between the modifier and the pseudoboehmite powder. It is sufficient to provide adequate space for the gas generated after the modifier decomposes to rise and diffuse. However, for ease of comparison, the same PTFE reactor is used in all the following embodiments and comparative examples. An adjustable-height PTFE support is placed inside the PTFE reactor to support the filter paper-covered pseudoboehmite layer. The support layer of the PTFE support in contact with the filter paper-covered pseudoboehmite layer has a perforated structure (ensuring the filter paper-covered pseudoboehmite layer is fixed and does not fall off) to facilitate gas permeation.

[0035] Evaluation method:

[0036] The pore structure and specific surface area of ​​the samples were determined using a Konta NOVA 2200e at 77 K. Before testing, the samples were degassed under vacuum at 300 °C for 6 h. Specific surface area was calculated using the Brunauer-Emmett-Teller (BET) method at five experimental points with a relative pressure range (P / P0) of 0.05–0.25. At P / P0 = 0.99, the total pore volume was calculated using the single-point adsorption method. The pore size distribution (PSD) of the samples was calculated using a non-local density functional theory (NLDFT) model. Micropore specific surface area and micropore volume were determined by t-plot analysis.

[0037] The surface morphology of the samples was observed using a scanning electron microscope (SEM, JSM-5600L) at 0.5–30 kV. Powder X-ray diffraction (PXRD) patterns were acquired using a PANalytical X'pert Pro MPD X-ray diffractometer under Cu Kα radiation (λ = 0.1540598 nm), within an angle range of 2θ = 5–75°, at 40 kV and 40 mA, with a scanning step size of 0.017°.

[0038] Example 1

[0039] Weigh ammonium bicarbonate and boehmite powder according to a molar ratio of ammonium bicarbonate to Al of 1.5, and set aside.

[0040] At room temperature, the weighed ammonium bicarbonate was placed at the bottom of a polytetrafluoroethylene (PTFE) reactor. Then, boehmite powder was wrapped in filter paper to form a boehmite powder layer (1 cm thick), which was then fixed onto the support layer of a PTFE support inside the reactor, ensuring the distance between the boehmite powder layer and the lower modifier layer was 4 cm. The PTFE reactor containing the reactants was then transferred to a sealed crystallization vessel and crystallized at 100°C for 24 hours. The solid product from the PTFE reactor was then removed and dried at 90°C for 20 hours to obtain the alumina precursor AACH-U-100-1.5 (basic aluminum ammonium carbonate, abbreviated as AACH), with a specific surface area of ​​594.0 m². 2 / g, pore volume 0.4cm 3 / g, with an average pore size of 1.7nm.

[0041] The alumina precursor AACH-U-100-1.5 was heated to 300°C under vacuum at a heating rate of 2°C / min, and then decomposed at 300°C for 2 hours. Afterward, it was placed in a muffle furnace and heated to 500°C at a heating rate of 2°C / min, and calcined at 500°C for 3 hours to obtain ultraporous alumina nanofibers Al2O3-U-100-1.5, whose specific surface area was measured to be 461.4 m². 2 / g, pore volume 0.4cm 3 / g, with an average pore size of 2.0nm.

[0042] Example 2

[0043] Weigh ammonium bicarbonate and boehmite powder according to a molar ratio of ammonium bicarbonate to Al of 4.5, and set aside.

[0044] At room temperature, the weighed ammonium bicarbonate was placed at the bottom of a polytetrafluoroethylene (PTFE) reactor. Then, boehmite powder was wrapped in filter paper to form a boehmite powder layer (1 cm thick), which was then fixed onto the support layer of a PTFE support inside the reactor, ensuring the distance between the boehmite powder layer and the lower modifier layer was 4 cm. The PTFE reactor containing the reactants was then transferred to a sealed crystallization vessel and crystallized at 100°C for 24 hours. The solid product from the PTFE reactor was then removed and dried at 90°C for 20 hours to obtain the alumina precursor AACH-U-100-4.5 (basic aluminum ammonium carbonate, abbreviated as AACH), with a specific surface area of ​​669.6 m². 2 / g, pore volume 0.5cm 3 / g, with an average pore size of 1.5nm.

[0045] The alumina precursor AACH-U-100-1.5 was heated to 300°C under vacuum at a heating rate of 2°C / min, and then decomposed at 300°C for 2 hours. Afterward, it was placed in a muffle furnace and heated to 500°C at a heating rate of 2°C / min, and calcined at 500°C for 3 hours to obtain ultraporous alumina nanofibers Al2O3-U-100-4.5, whose specific surface area was measured to be 515.3 m². 2 / g, pore volume 0.4cm 3 / g, with an average pore size of 1.9nm.

[0046] Example 3

[0047] Weigh ammonium bicarbonate and boehmite powder according to a molar ratio of ammonium bicarbonate to Al of 7.5, and set aside.

[0048] At room temperature, the weighed ammonium bicarbonate was placed at the bottom of a polytetrafluoroethylene (PTFE) reactor. Then, boehmite powder was wrapped in filter paper to form a boehmite powder layer (1 cm thick), which was then fixed onto the support layer of a PTFE support inside the reactor, ensuring the distance between the boehmite powder layer and the lower modifier layer was 4 cm. The PTFE reactor containing the reactants was then transferred to a sealed crystallization vessel and crystallized at 100°C for 24 hours. The solid product from the PTFE reactor was then removed and dried at 90°C for 20 hours to obtain the alumina precursor AACH-U-100-7.5 (basic aluminum ammonium carbonate, abbreviated as AACH), with a specific surface area of ​​684.0 m². 2 / g, pore volume 0.5cm 3 / g, with an average pore size of 1.4nm.

[0049] The alumina precursor AACH-U-100-1.5 was heated to 300°C under vacuum at a heating rate of 2°C / min, and then decomposed at 300°C for 2 hours. Afterward, it was placed in a muffle furnace and heated to 500°C at a heating rate of 2°C / min, and calcined at 500°C for 3 hours to obtain ultraporous alumina nanofibers Al2O3-U-100-7.5, with a specific surface area of ​​544.7 m². 2 / g, pore volume 0.5cm 3 / g, with an average pore size of 2.3nm.

[0050] Example 4

[0051] Weigh ammonium carbonate and boehmite powder according to a molar ratio of ammonium carbonate to Al of 1.5, and set aside.

[0052] At room temperature, the weighed ammonium carbonate was placed at the bottom of a polytetrafluoroethylene (PTFE) reactor. Then, boehmite powder was wrapped in filter paper to form a boehmite powder layer (1 cm thick), which was then fixed onto the support layer of a PTFE support inside the reactor, ensuring the distance between the boehmite powder layer and the lower modifier layer was 4 cm. The PTFE reactor containing the reactants was then transferred to a sealed crystallization vessel and crystallized at 100°C for 24 hours. The solid product from the PTFE reactor was then removed and dried at 100°C for 12 hours to obtain the alumina precursor AACH-A-100-1.5 (basic aluminum ammonium carbonate, abbreviated as AACH), with a specific surface area of ​​413.9 m². 2 / g, pore volume 0.3cm 3 / g, with an average pore size of 1.9nm.

[0053] The aforementioned alumina precursor AACH-A-100-1.5 was heated to 300°C under vacuum at a heating rate of 2°C / min, and then decomposed at 300°C for 2 hours. Afterward, it was placed in a muffle furnace and heated to 500°C at a heating rate of 2°C / min, and calcined at 500°C for 3 hours to obtain ultraporous alumina nanofibers Al2O3-A-100-1.5, whose specific surface area was measured to be 357.6 m². 2 / g, pore volume 0.4cm 3 / g, with an average pore size of 2.1nm.

[0054] Example 5

[0055] Weigh ammonium carbonate and boehmite powder according to a molar ratio of ammonium carbonate to Al of 4.5, and set aside.

[0056] At room temperature, the weighed ammonium carbonate was placed at the bottom of a polytetrafluoroethylene (PTFE) reactor. Then, boehmite powder was wrapped in filter paper to form a boehmite powder layer (1 cm thick), which was then fixed onto the support layer of a PTFE support inside the reactor, ensuring the distance between the boehmite powder layer and the lower modifier layer was 4 cm. The PTFE reactor containing the reactants was then transferred to a sealed crystallization vessel and crystallized at 100°C for 24 hours. The solid product from the PTFE reactor was then removed and dried at 100°C for 12 hours to obtain the alumina precursor AACH-A-100-4.5 (basic aluminum ammonium carbonate, abbreviated as AACH), with a specific surface area of ​​564.6 m². 2 / g, pore volume 0.5cm 3 / g, with an average pore size of 1.7nm.

[0057] The aforementioned alumina precursor AACH-A-100-4.5 was heated to 300°C under vacuum at a heating rate of 2°C / min, and then decomposed at 300°C for 2 hours. Afterward, it was placed in a muffle furnace and heated to 500°C at a heating rate of 2°C / min, and calcined at 500°C for 3 hours to obtain ultraporous alumina nanofibers Al2O3-A-100-4.5, whose specific surface area was measured to be 453.5 m². 2 / g, pore volume 0.4cm 3 / g, with an average pore size of 2.0nm.

[0058] Example 6

[0059] Weigh ammonium carbonate and boehmite powder according to a molar ratio of ammonium carbonate to Al of 7.5, and set aside.

[0060] At room temperature, the weighed ammonium carbonate was placed at the bottom of a polytetrafluoroethylene (PTFE) reactor. Then, boehmite powder was wrapped in filter paper to form a boehmite powder layer (1 cm thick), which was then fixed onto the support layer of a PTFE support inside the reactor, ensuring the distance between the boehmite powder layer and the lower modifier layer was 4 cm. The PTFE reactor containing the reactants was then transferred to a sealed crystallization vessel and crystallized at 100°C for 24 hours. The solid product from the PTFE reactor was then removed and dried at 100°C for 12 hours to obtain the alumina precursor AACH-A-100-7.5 (basic aluminum ammonium carbonate, abbreviated as AACH), with a specific surface area of ​​648.4 m². 2 / g, pore volume 0.4cm 3 / g, with an average pore size of 1.6nm.

[0061] The alumina precursor AACH-A-100-7.5 was heated to 300°C under vacuum at a heating rate of 2°C / min, and then decomposed at 300°C for 2 hours. Afterward, it was placed in a muffle furnace and heated to 500°C at a heating rate of 2°C / min, and calcined at 500°C for 3 hours to obtain ultraporous alumina nanofibers Al2O3-A-100-7.5, with a specific surface area of ​​490.5 m². 2 / g, pore volume 0.4cm 3 / g, with an average pore size of 1.9nm.

[0062] Example 7

[0063] Weigh ammonium carbonate and boehmite powder according to a molar ratio of ammonium carbonate to Al of 20, and set aside.

[0064] At room temperature, the weighed ammonium carbonate was placed at the bottom of a polytetrafluoroethylene (PTFE) reactor. Then, boehmite powder was wrapped in filter paper to form a boehmite powder layer (1 cm thick), which was then fixed onto the support layer of a PTFE support inside the reactor, ensuring the distance between the boehmite powder layer and the lower modifier layer was 4 cm. The PTFE reactor containing the reactants was then transferred to a sealed crystallization vessel and crystallized at 100°C for 24 hours. The solid product from the PTFE reactor was then removed and dried at 100°C for 12 hours to obtain the alumina precursor AACH-A-100-20 (basic aluminum ammonium carbonate, abbreviated as AACH), with a specific surface area of ​​667.5 m². 2 / g, pore volume 0.6cm 3 / g, with an average pore size of 1.6nm.

[0065] The alumina precursor AACH-A-100-20 was heated to 300°C under vacuum at a heating rate of 2°C / min, and then decomposed at 300°C for 2 hours. Afterward, it was placed in a muffle furnace and heated to 500°C at a heating rate of 2°C / min, and calcined at 500°C for 3 hours to obtain ultraporous alumina nanofibers Al2O3-A-100-20, whose specific surface area was measured to be 520.4 m². 2 / g, pore volume 0.4cm 3 / g, with an average pore size of 1.9nm.

[0066] Comparative Example 1

[0067] Weigh ammonium bicarbonate and boehmite powder according to a molar ratio of ammonium bicarbonate to Al of 1.5, and set aside.

[0068] At room temperature, the weighed ammonium bicarbonate was mixed evenly with the pseudoboehmite dry powder and placed at the bottom of a polytetrafluoroethylene (PTFE) reactor. The PTFE reactor containing the reactants was then transferred to a sealed crystallization vessel and crystallized at 100°C for 24 hours. The solid product from the PTFE reactor was then removed and dried at 90°C for 20 hours to obtain the alumina precursor AACH-C-100-1.5 (basic aluminum ammonium carbonate, abbreviated as AACH). The specific surface area was measured to be 342.1 m². 2 / g, pore volume 0.5cm 3 / g, with an average pore size of 2.4nm.

[0069] The alumina precursor AACH-C-100-1.5 was heated to 300°C under vacuum at a heating rate of 2°C / min, and then decomposed at 300°C for 2 hours. Afterward, it was placed in a muffle furnace and heated to 500°C at a heating rate of 2°C / min, and calcined at 500°C for 3 hours to obtain ultraporous alumina nanofibers Al2O3-C-100-1.5, whose specific surface area was measured to be 302.5 m². 2 / g, pore volume 0.5cm 3 / g, with an average pore size of 2.8nm.

[0070] Among them, the N2 adsorption-desorption isotherms of AACH prepared in Examples 1-7 are as follows: Figure 1 As shown, by Figure 1 It can be seen that the sample has a high adsorption capacity in the low pressure region, which indicates that the sample has a high specific surface area. The adsorption isotherm of the sample is close to that of type I, which indicates the microporous characteristics of the material. However, the material also has a narrow hysteresis loop, which indicates that small mesopores exist in the material at the same time.

[0071] The pore size distribution curves of AACH prepared in Examples 1-7 are shown in the figure below. Figure 2 As shown, by Figure 2 It can be seen that the pore size of the sample is mainly distributed in 1-2 nm, which proves its ultra-microporous characteristics, but there are also a small number of pores larger than 2 nm, making its average pore size greater than 2 nm.

[0072] The XRD diffraction patterns of AACH prepared in Examples 1-3 are as follows: Figure 3 As shown, by Figure 3 It can be seen that the sample has high crystallinity and no other impurity peaks can be observed in the XRD, indicating the successful synthesis of the alumina precursor AACH.

[0073] The XRD diffraction patterns of AACH prepared in Examples 4-7 are as follows: Figure 4 As shown, by Figure 4 It can be seen that the sample only shows the diffraction peak of AACH, and the intensity of the diffraction peak gradually increases with the increase of the amount of modifier.

[0074] The N2 adsorption-desorption isotherms of the ultraporous alumina nanofibers prepared in Examples 1-3 are as follows: Figure 5 As shown, by Figure 5 It can be seen that the adsorption capacity of the sample is still relatively high in the low-pressure region, indicating that the sample still has a high specific surface area after treatment.

[0075] The pore size distribution curves of the ultramicroporous alumina nanofibers prepared in Examples 1-3 are shown in the figure. Figure 6 As shown, by Figure 6 It can be seen that the pore size of the sample is mainly distributed in the range of 1-2 nm, which further illustrates the ultraporous characteristics of the material.

[0076] The XRD diffraction patterns of the ultraporous alumina nanofibers prepared in Examples 1-3 are as follows: Figure 7 As shown, by Figure 7 It can be seen that the sample is mainly in an amorphous state.

[0077] SEM images of the ultraporous alumina nanofibers prepared in Examples 2-3 are shown below. Figure 8 As shown, by Figure 8 It is known that the sample is fibrous, which provides the basis for the sample having a high specific surface area.

[0078] Of course, the present invention may have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications according to the present invention, but these corresponding changes and modifications should all fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing ultraporous alumina nanofibers, characterized in that, Includes the following steps: The modifier was placed at the bottom of the polytetrafluoroethylene reactor. The pseudoboehmite dry powder was wrapped in filter paper and placed on the upper layer of the polytetrafluoroethylene reactor and fixed. Then the polytetrafluoroethylene reactor was placed in a sealed crystallization kettle for crystallization reaction and dried to obtain the alumina precursor. The alumina precursor was decomposed by vacuum heating and then calcined to obtain the ultra-microporous alumina nanofibers. The preparation method synthesized alumina with an ultraporous structure via a solid-state method. The modifier is an ammonium salt; The molar ratio of the modifier to the Al element in the pseudoboehmite is 1.5~20:1; The crystallization reaction is carried out at a temperature of 50~180℃ for a reaction time of 6~48h.

2. The method for preparing ultraporous alumina nanofibers according to claim 1, characterized in that, The ammonium salt is selected from at least one of ammonium carbonate, ammonium bicarbonate, ammonium acetate, ammonium carbamate, ammonium oxalate, ammonium formate, ammonium citrate, and ammonium tartrate.

3. The method for preparing ultraporous alumina nanofibers according to claim 1, characterized in that, The drying temperature is 60~200℃.

4. The method for preparing ultraporous alumina nanofibers according to claim 1, characterized in that, The alumina precursor is subjected to vacuum thermal decomposition at a temperature of 150~350℃ for 1~5h, with a heating rate of 1~10℃ / min.

5. The method for preparing ultraporous alumina nanofibers according to claim 1, characterized in that, The roasting temperature is 400~800℃ and the time is 2~6h.

Citation Information

Patent Citations

  • Super-microporous high-specific surface area aluminium oxide material and preparation method thereof

    CN103073036A

  • Green technology for synthesizing ammonium aluminum carbonate hydroxide and pyrolysis thereof to prepare high specific surface alumina

    CN109292802A

  • Process for synthesizing monoclinic-phase basic ammonium aluminum carbonate and preparing porous aluminum oxide through pyrolysis of the monoclinic-phase basic ammonium aluminum carbonate

    CN111233017A

  • Method for synthesizing super-microporous ammonium aluminium carbonate hydroxide and preparing alumina by pyrolyzing ammonium aluminium carbonate hydroxide

    CN108217702A